Using Tillandsia usneoides as Biomonitor for Toxic Metals in the Air of Guanajuato’s Tunnel Network - Brito, Elcia Margareth Souza; Zarate-Santoyo, Pedro Antonio; Caretta, César Augusto; Lino, Adan Santos; Valerdi-Negreros, Júlio César; Torres, João Paulo Machado; Malm, Olaf (Orbital: The Electronic Journal of Chemistry, 2024)
Guanajuato town is an important touristic center of Mexico, and one of its main attractions is its tunnel network (subterranean streets). In this work the air quality inside this tunnel network was evaluated using samples of Tillandsia usneoides as a biomonitor. Twenty-one plastic passive samplers, containing 50 g of plants each, were installed at different points of this tunnel network. In addition, surface layer of the tunnel walls, close to the plant sampling sites, were collected. Estimates for the enrichment factor, using Fe as reference and standard metal crustal data, suggest that the origin of the suspended metals is probably geogenic for Cr, a mix for Cu, and anthropogenic for Zn and Hg. It is important to emphasize that the Guanajuato’s tunnel network is used both by pedestrians and vehicular traffic and, probably, the last one is acting as the main source for toxic elements for the tunnel’s air.